Grand Canyon (Washington, D.C. : National Geographic, 2009)
Explores the untamed wilderness of Grand Canyon National Park rarely seen by most park visitors.
Features: Grand Canyon Explorer 3D interactive and printable map.
Originally broadcast on television on the National Geographic channel in [200-?].
DVD.
Keywords: National parks and reserves -- United States; Grand Canyon National Park (Ariz.); Documentary television programs; Nonfiction television programs; Travel programs